PEMBUATAN PETA SITUASI DUSUN BANARAN DAN TRUKAN, DESA BANYURIPAN, KECAMATAN BAYAT, KABUPATEN KLATEN, PROPINSI JAWA TENGAH - , SITI A. NOVIAJAYANTI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Field Work in the District implemented Bayat Klaten regency, Central Java Province, is one of the subjects that the students must be taken 3 Diploma Geomatics Engineering as a final project which is one of the requirements to obtain a degree graduation Associate Expert (A.Md.) . Activities conducted on the Field Work in the form of mapping work to generate spatial data information from the earth's surface. Spatial data covering the high point and planimetric detail obtained from measurements of the earth's surface which is presented in map form. The measurement is done by measuring the horizontal control framework, vertical control framework, the measurement of planimetric detail and high detail as well done depiction of the digital map to generate map situation. Of all the Field Work activities that have been implemented can be completed on time with the results of measurements and calculations KKH and KKV that meet the specifications of the implementation of PKL (TOR). Results obtained in the form of a four sheet map of the situation with the scale of 1: 500 were present spatial data on the earth's surface area and Trukan Banaran Hamlet, Village Banyuripan, District Bayat, Klaten Regency, Central Java Province.